Virtual Photography: Artificial Intelligence, In-game, and Extended Reality (transcript Verlag, 2024)
While it has traditionally been seen as a means of documenting an external reality or expressing an internal feeling, photography is now capable of actualizing never-existed pasts and never-lived experiences. Thanks to the latest photographic technologies, we can now take photos in computer games, interpolate them in extended reality platforms, or synthesize them via artificial intelligence. To account for the most recent shifts in conceptualizations of photography, this book proposes the term virtual photography as a binding theoretical framework, defined as a photography that retains the efficiency and function of real photography (made with or without a camera) while manifesting these in an unfamiliar or noncustomary form.